An Empirical Analysis of Remittances, Foreign Direct Investment and Sovereign Debt on Economic Growth in Nigeria - Anthony Oyamendan (Universitas Indonesia Membangun, 2025)
This study investigated the effects of remittances (REM), foreign direct investment (FDI), and sovereign debt (DEBT) on economic development (GDP) in Nigeria from 1990 to 2023. The objectives are to examine the long- and short-run impacts of REM, FDI, and DEBT on GDP, determine the direction of causality among these variables, and provide policy recommendations for sustainable economic growth. Descriptive statistics show that remittances averaged 5.41% of GDP, FDI 2.76%, and sovereign debt 35.82%, highlighting varying contributions to economic performance. Stationarity tests confirm mixed integration, validating the use of the ARDL bounds testing approach. The ARDL cointegration test reveals a long-run equilibrium relationship among the variables. Long-run ARDL results indicate that a 1% increase in remittances and FDI leads to approximately 0.31% and 0.22% increases in GDP, respectively, while a 1% increase in sovereign debt reduces GDP by about 0.18%. Short-run Error Correction Model results show that remittances and FDI contribute 0.12% and 0.09% to GDP growth per 1% change, respectively, with an ECM coefficient of -0.641, suggesting 64% of disequilibrium is corrected annually. Granger causality analysis confirms unidirectional causality from REM and FDI to GDP. The study concludes that remittances and FDI are significant growth drivers, whereas excessive debt hampers long-term development. Policy recommendations include optimizing remittance utilization, attracting productive FDI, and ensuring prudent debt management.